Both Natural and Induced Anti-Sda Antibodies Play Important Roles in GTKO Pig-to-Rhesus Monkey Xenotransplantation - Feng, Hao; Li, Tao; Du, Jiaxiang; Xia, Qiangbing; Wang, Lu; Chen, Song; Zhu, Lan; Pan, Dengke; Wang, Yi; Chen, Gang (Frontiers in Immunology, 2022)
Sda, produced by the B4GALNT2 enzyme, has been recognized as an important xenoantigen for pig-to-nonhuman primate xenotransplantation. However, little is known about Sda expression in pigs and its immunogenicity in xenotransplantation. In this study, peripheral blood mononuclear cells (PBMCs) were isolated from wildtype, GTKO (with high, moderate, and low Sda expression), GTKO/β4GalNT2KO, GTKO/CMAHKO, or GTKO/CMAHKO/β4GalNT2KO pigs. Anti-pig IgM/IgG binding and complement-dependent cytotoxicity (CDC) to pig PBMCs was measured by flow cytometry using pooled rhesus monkey sera (n=20) or human sera (n=20). As compared to wild-type pigs (n=12), GTKO pigs (n=17) had a significantly higher mean level of Sda expression on PBMCs and showed a greater individual difference in expression. Both the overall binding of monkey serum IgM/IgG antibody to GTKO pig PBMCs and CDC against these PBMCs decreased significantly with a progressive reduction in Sda expression, showing a clear dose-effect relationship. Both the monkey serum antibody binding and CDC decreased significantly after the additional deletion of Sda, whereas the binding of human serum antibody and CDC against the GTKO pig PBMCs were markedly reduced after the deletion of Neu5Gc in the pigs. In addition, anti-Sda antibody accounted for > 50% of the induced anti-non-Gal antibody at the time of rejection in two rhesus monkeys that received GTKO/hCD55 pig kidney xenotransplantation, and the anti-Sda antibody showed significant cytotoxic activity against GTKO pig cells. We conclude that both natural and induced anti-Sda antibodies play important roles in GTKO pig-to-rhesus monkey xenotransplantation, thus providing further evidence for GTKO/β4GalNT2KO pigs as the preferred organ source for rhesus monkeys as a preclinical model of xenotransplantation.